Breaking the taboo: an interpretative phenomenological analysis of healthcare professionals' experience of caring for palliative patients with disgusting symptoms. Issue 2 (8th October 2014) - Muggleton, Joshua; Guy, Helen; Howard, Ruth
Abstract : Objectives: Disgusting symptoms are common in healthcare settings. Previous research has identified that healthcare professionals systematically avoid contact with patients with disgusting symptoms, potentially compromising patient care. Furthermore, research has highlighted disgust in healthcare professionals as a possible contributory factor to dehumanisation and abuse of patients. Given that healthcare professionals often feel that disgust is unprofessional, they may also feel unable to express or process disgust in their work, potentially impacting their emotional health, and contributing to burning out. Given the ubiquity of disgust in palliative care, we investigated how palliative healthcare professionals' experience and cope with disgust in their work, and how they are supported in doing so. Methods and Results: We interviewed six palliative healthcare professionals and analysed their transcripts using Interpretative Phenomenological Analysis, from which four themes are discussed. Conclusions: Three key findings emerged. Firstly, participants were uncomfortable talking about disgust at work, reducing their access to support for disgust. Secondly, participants often neglected their own emotional needs, and as a result, sometimes become emotionally entangled with patients. Finally, participants were at risk of reducing vital socio-emotional support for patients with disgusting symptoms. Based on our analysis, we suggest interventions to counteract these effects.